2012
DOI: 10.1136/bmjopen-2012-001075
|View full text |Cite
|
Sign up to set email alerts
|

Jurisdictional, socioeconomic and gender inequalities in child health and development: analysis of a national census of 5-year-olds in Australia

Abstract: ObjectivesEarly child development may have important consequences for inequalities in health and well-being. This paper explores population level patterns of child development across Australian jurisdictions, considering socioeconomic and demographic characteristics.DesignCensus of child development across Australia.Setting and participantsTeachers complete a developmental checklist, the Australian Early Development Index (AEDI), for all children in their first year of full-time schooling. Between May and July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 38 publications
5
77
1
Order By: Relevance
“…So a simple apt modulator is essential to determine the prevailing health status in the communities aiming to resist malnutrition influencing factors and so the Equation 9 can be the easier option to choose in assessing the overall health status. The German chemist Friedrich Wohler, the pioneer of organic chemistry disapproves the vitalism inventing Wohler synthesis in 1828 (Brinkman et al, 2012;Wohler, 1828). The current study findings similarly can overlap the place of the BMI (Wohler, 1828) in health science.…”
Section: Discussionsupporting
confidence: 63%
“…So a simple apt modulator is essential to determine the prevailing health status in the communities aiming to resist malnutrition influencing factors and so the Equation 9 can be the easier option to choose in assessing the overall health status. The German chemist Friedrich Wohler, the pioneer of organic chemistry disapproves the vitalism inventing Wohler synthesis in 1828 (Brinkman et al, 2012;Wohler, 1828). The current study findings similarly can overlap the place of the BMI (Wohler, 1828) in health science.…”
Section: Discussionsupporting
confidence: 63%
“…A large US study of 22,797 children 1-5 years found that limited perceived access to amenities (recreation/community center, library, sidewalks, park/playground) was associated with less time spent in peer play and fewer family outings (Kenney, 2012). Furthermore, in Australia, differences in developmental vulnerability (children who score o10th percentile of the national AEDC population) across states and territories existed even after adjusting for sociodemographic factors and some of these differences were explained by the different mix of services that support children and families from birth to school age (Brinkman et al, 2012).…”
Section: Access To Child-relevant Destinations and Servicesmentioning
confidence: 87%
“…Four studies reported a significant association between domains of early child development and the presence of child relevant neighborhood destinations (e.g., recreation center, library, school) and services (e.g., child care centers) (Kenney, 2012;Fan and Chen, 2012;Brinkman et al, 2012;Rosenberg et al, 2011). A large US study of 22,797 children 1-5 years found that limited perceived access to amenities (recreation/community center, library, sidewalks, park/playground) was associated with less time spent in peer play and fewer family outings (Kenney, 2012).…”
Section: Access To Child-relevant Destinations and Servicesmentioning
confidence: 99%
“…Recording of developmental problems was also twofold higher in remote than non-remote primary care centres. This disparity is due to the high levels of risk and disadvantage experienced by many remote area indigenous children 37. Encouragingly, a high proportion of children with developmental problems received follow-up in all our primary care centres.…”
Section: Discussionmentioning
confidence: 99%